DESIGNING AN ACCOUNTING RECORD AND FINANCIAL REPORTING SYSTEM AT DURIAN KING - Sukiantono Tang; Lina Wati (Universitas Internasional Batam, 2022)
Lack of human resources understanding accounting and lack of knowledge is the main problem at durian king. This causes all Durian King’s financial transactions to be previously handled manually. This activity will be started with a survey and interviewing activities to analyze Durian King’s operations, implementation, and evaluation. This project has created a recording and accounting reporting using the Microsoft Access program. The system that has been designed aims to make it easier to record durian king's daily transactions, and help to find out the company's profits, expenses and it will automatically generate financial reports. The financial reports are expected to produce accurate and reliable reports so that these financial statements can be used as a reference for companies in making decisions